Exercise-induced bronchodilation is not impacted by beta-adrenergic receptor blockade in males or females - Connor J. Doherty; Benjamin P. Thompson; Paige J. Rynne; Jou-Chung Chang; Sarah A. Angus; Armando J. Aguero; Sean L. Gartner; Paolo Dominelli (European Journal of Applied Physiology, 2026)

Epilithic algal composition and the functioning of Anthropocene coral reefs - Sterling B. Tebbett; Michael J. Emslie; Michelle J. Jonker; Scott D. Ling; Morgan S. Pratchett; Alexandre C. Siqueira; Angus A. Thompson; Helen F. Yan; David R. Bellwood (Marine Pollution Bulletin, 2025)

Predictors of long-term variability in NE Atlantic plankton communities - Matthew M. Holland; Angus Atkinson; Mike Best; Eileen Bresnan; Michelle Devlin; Eric Goberville; Pierre Hélaouët; Margarita Machairopoulou; Matthew Faith; Murray S.A. Thompson; Abigail McQuatters-Gollop (Science of The Total Environment, 2024)

Transient dynamics mask the resilience of coral reefs - Karlo Hock; Alan Hastings; Christopher Doropoulos; Russell C. Babcock; Juan C. Ortiz; Angus Thompson; Peter J. Mumby (Theoretical Ecology, 2024)
Coral reefs are model systems for studies of ecological resilience, with communities generally exhibiting multiple stable states and more resilient regions trending towards a single, coral-dominated, regime. We expand the theory of ecological resilience beyond the concepts of distinct stable states to integrate emerging ideas from transient dynamics as long-term intermediate states with no pronounced trend towards equilibria. We show that low coral abundance, together with stochastic larval supply and disturbance, can trap otherwise resilient reefs in a persistent intermediate state whose long-term outcome is difficult to predict. Common metrics, such as the ecosystem slowing down before crossing tipping points and using historical coral cover trends, may become unreliable predictors of future behaviour. Helping reefs out of transient states requires agile management that allows for short-term, targeted interventions after which natural ecological feedbacks can take over.

Habitat size influences community stability - Hamish S. Greig; Peter A. McHugh; Ross M. Thompson; Helen J. Warburton; Angus R. McIntosh (Ecology, 2022)
Mechanisms linked to demographic, biogeographic, and food‐web processes thought to underpin community stability could be affected by habitat size, but the effects of habitat size on community stability remain relatively unknown. We investigated whether those habitat‐size‐dependent properties influenced community instability and vulnerability to perturbations caused by disturbance. This is particularly important given that human exploitation is contracting ecosystems, and abiotic perturbations are becoming more severe and frequent. We used a perturbation experiment in which 10 streams, spanning three orders of magnitude in habitat size, were subjected to simulated bed movement akin to a major flood disturbance event. We measured the resistance, resilience, and variability of basal resources, and population and community‐level responses across the stream habitat‐size gradient immediately before, and at 0.5, 5, 10, 20, and 40 d post‐disturbance. Resistance to disturbance consistently increased with stream size in all response variables. In contrast, resilience was significantly higher in smaller streams for some response variables. However, this higher resilience of small ecosystems was insufficient to compensate for their lower resistance, and communities of smaller streams were thus more variable over time than those of larger streams. Compensatory dynamics of populations, especially for predators, stabilized some aspects of communities, but these mechanisms were unrelated to habitat size. Together, our results provide compelling evidence for the links between habitat size and community stability, and should motivate ecologists and managers to consider how changes in the size of habitats will alter the vulnerability of ecosystems to perturbations caused by environmental disturbance.

Shifts in coralline algae, macroalgae, and coral juveniles in the Great Barrier Reef associated with present‐day ocean acidification - Joy N. Smith; Mathieu Mongin; Angus Thompson; Michelle J. Jonker; Glenn De'ath; Katharina E. Fabricius (Global Change Biology, 2020)
Seawater acidification from increasing CO 2 is often enhanced in coastal waters due to elevated nutrients and sedimentation. Our understanding of the effects of ocean and coastal acidification on present‐day ecosystems is limited. Here we use data from three independent large‐scale reef monitoring programs to assess coral reef responses associated with changes in mean aragonite saturation state (Ω ar ) in the Great Barrier Reef World Heritage Area (GBR). Spatial declines in mean Ω ar are associated with monotonic declines in crustose coralline algae (up to 3.1‐fold) and coral juvenile densities (1.3‐fold), while non‐calcifying macroalgae greatly increase (up to 3.2‐fold), additionally to their natural changes across and along the GBR. These three key groups of organisms are important proxies for coral reef health. Our data suggest a tipping point at Ω ar 3.5–3.6 for these coral reef health indicators. Suspended sediments acted as an additive stressor. The latter suggests that effective water quality management to reduce suspended sediments might locally and temporarily reduce the pressure from ocean acidification on these organisms.

Co-creating a knowledge base in the “22q11.2 deletion syndrome” community - Roberta Rizzo; Marianne Van den Bree; Aimee Challenger; Andrew Cuthbert; Michael Arribas Ayllon; Angus Clarke; Rose Thompson (Journal of Community Genetics, 2020)

Spatial resilience of the Great Barrier Reef under cumulative disturbance impacts - Camille Mellin; Samuel Matthews; Kenneth R.N. Anthony; Stuart C. Brown; M. Julian Caley; Kerryn A. Johns; Kate Osborne; Marjetta Puotinen; Angus Thompson; Nicholas H. Wolff; Damien A. Fordham; M. Aaron MacNeil (Global Change Biology, 2019)
In the face of increasing cumulative effects from human and natural disturbances, sustaining coral reefs will require a deeper understanding of the drivers of coral resilience in space and time. Here we develop a high‐resolution, spatially explicit model of coral dynamics on Australia's Great Barrier Reef (GBR). Our model accounts for biological, ecological and environmental processes, as well as spatial variation in water quality and the cumulative effects of coral diseases, bleaching, outbreaks of crown‐of‐thorns starfish ( Acanthaster cf. solaris ), and tropical cyclones. Our projections reconstruct coral cover trajectories between 1996 and 2017 over a total reef area of 14,780 km 2 , predicting a mean annual coral loss of −0.67%/year mostly due to the impact of cyclones, followed by starfish outbreaks and coral bleaching. Coral growth rate was the highest for outer shelf coral communities characterized by digitate and tabulate Acropora spp. and exposed to low seasonal variations in salinity and sea surface temperature, and the lowest for inner‐shelf communities exposed to reduced water quality. We show that coral resilience (defined as the net effect of resistance and recovery following disturbance) was negatively related to the frequency of river plume conditions, and to reef accessibility to a lesser extent. Surprisingly, reef resilience was substantially lower within no‐take marine protected areas, however this difference was mostly driven by the effect of water quality. Our model provides a new validated, spatially explicit platform for identifying the reefs that face the greatest risk of biodiversity loss, and those that have the highest chances to persist under increasing disturbance regimes.

Delayed coral recovery in a warming ocean - Kate Osborne; Angus A. Thompson; Alistair J. Cheal; Michael J. Emslie; Kerryn A. Johns; Michelle J. Jonker; Murray Logan; Ian R. Miller; Hugh P. A. Sweatman (Global Change Biology, 2017)
Climate change threatens coral reefs across the world. Intense bleaching has caused dramatic coral mortality in many tropical regions in recent decades, but less obvious chronic effects of temperature and other stressors can be equally threatening to the long‐term persistence of diverse coral‐dominated reef systems. Coral reefs persist if coral recovery rates equal or exceed average rates of mortality. While mortality from acute destructive events is often obvious and easy to measure, estimating recovery rates and investigating the factors that influence them requires long‐term commitment. Coastal development is increasing in many regions, and sea surface temperatures are also rising. The resulting chronic stresses have predictable, adverse effects on coral recovery, but the lack of consistent long‐term data sets has prevented measurement of how much coral recovery rates are actually changing. Using long‐term monitoring data from 47 reefs spread over 10 degrees of latitude on Australia's Great Barrier Reef ( GBR ), we used a modified Gompertz equation to estimate coral recovery rates following disturbance. We compared coral recovery rates in two periods: 7 years before and 7 years after an acute and widespread heat stress event on the GBR in 2002. From 2003 to 2009, there were few acute disturbances in the region, allowing us to attribute the observed shortfall in coral recovery rates to residual effects of acute heat stress plus other chronic stressors. Compared with the period before 2002, the recovery of fast‐growing Acroporidae and of “Other” slower growing hard corals slowed after 2002, doubling the time taken for modest levels of recovery. If this persists, recovery times will be increasing at a time when acute disturbances are predicted to become more frequent and intense. Our study supports the need for management actions to protect reefs from locally generated stresses, as well as urgent global action to mitigate climate change.

Coral community responses to declining water quality: Whitsunday Islands, Great Barrier Reef, Australia - Angus Thompson; Thomas Schroeder; Vittorio E. Brando; Britta Schaffelke (Coral Reefs, 2014)

Comparative adherence to oxybutynin or tolterodine among older patients - Angus Thompson (European Journal of Clinical Pharmacology, 2012)

Correlation between extent of osteolytic damage and metastatic burden of human breast cancer metastasis in nude mice: Real-time PCR quantitation - Angus M. Tester; Julie A. Sharp; Nirada Dhanesuan; Mark Waltham; Erik W. Thompson (Clinical & Experimental Metastasis, 2002)

MMP-9 secretion and MMP-2 activation distinguish invasive and metastatic sublines of a mouse mammary carcinoma system showing epithelial-mesenchymal transition traits - Angus M. Tester; Neeracha Ruangpanit; Robin L. Anderson; Erik W. Thompson (Clinical & Experimental Metastasis, 2000)